(3QSGdI aj GdGLJgGO hGdENHGQs - (3GdHgHgGfj, GdCSJGP GdCcHQ, GdhMjO, eMeO HGbQ Hf eMeO Cced, (B1206 (3g`s ((3eMeO bGSe Hf eMeO GdOfHRj GdfLajs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3hQJHJgG Ydi SHYI aUhd GdChd GYde Cf Gddg JYGdi de jNdb GdNdb YHKG hdG jegdge SOi Hd Ndbge HbOQJg hLYd dge CSeGYG hCHUGQG hbdhHG hCdHGHG Ke HYK Edjge GdfHjjf jCeQhfge HWGYJg hjfghfge Yf eYUjJg (B...s
(3BNQgG (B:s
... (3hHGdLedI GTHGY GdcdGe aj GdebGe hGdJhMjg Edi LejY eG jJYdb HGdGLJgGO hGdJbdjO jhLH GdedGd aGdGbJUGQ Ydi eG MQQfG Chdi hGdYGbd Jcajg GdETGQI hjecfg GSJYdGe GdMGd aj cd hGMO efgG HYO edGMXI eG PcQfG (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\ 49s
(3GdPQjYI (B1\1415s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs